The Influence of Brand Image: Brand Hate-Brand Love on The Purchase of BMW Luxury Cars - Muhammad Khairil Bustaman; Rima Elya Dasuki (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2022)
BMW is currently the leader in selling premium class cars in Indonesia. This illustrates that BMW cars can be an indicator that they are still a secondary choice desired by consumers in buying premium cars. The focus of this paper is to analyze the influence of brand image, brand hate and brand love on the decision to buy a car. The respondents of this research will be direct buyers and users of BMW in West Java, with age criteria above 21 years. To measure the decision to buy a BMW car analysis variable including product quality, perceived value, fairness of price and brand image, where brand image is suspected variable with the most dominant variable influencing customer buying decisions. Methods of data analysis to be carried out using reliability tests and validity tests. This paper is the basis of research that will be carried out related to purchasing decisions and brand image where this will help the implementation of research to be more planned and structured.